SOA Governance from an Enterprise Architecture Viewpoint - Diirr, Thaíssa; Azevedo, Leonardo Guerreiro; Santoro, Flávia Maria (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2014: Anais do X Simpósio Brasileiro de Sistemas de Informação, 2014)
To obtain business benefits resulting from the implementation of an SOA approach is not sufficient managing technical features. A strategy aligned to business should be considered as a basis for activities of implementation, validation,development and services management. A business case, a reference model and anarchitecture of the organization should be established. This paper proposes SOAgovernance processes. The processes were evaluated by SOA experts who argue thatthey would adopt them for SOA governance in their organizations.